Circulating TSLP associates with decreased wheezing in non‐atopic preschool children: data from the URECA birth cohort. Issue 6 (June 2014) - Demehri, S.; Yockey, L. J.; Visness, C. M.; Jaffee, K. F.; Turkoz, A.; Wood, R. A.; O'Connor, G. T.; Kattan, M.; Gern, J. E.; Gergen, P. J.; Holtzman, M.; Bloomberg, G.; et al.
Summary Background Mouse models of atopic march suggest that systemic, skin‐derived thymic stromal lymphopoietin (TSLP) mediates progression from eczema to asthma. Objective We investigated whether circulating TSLP is associated with eczema, allergic sensitization, or recurrent wheezing in young children. Methods A prospective analysis of the relationship between plasma levels of TSLP to allergic sensitization and recurrent wheezing was conducted in the birth cohort from the Urban Environment and Childhood Asthma (URECA) study. Plasma TSLP levels were measured at 1, 2, and 3 years of age and analysed for correlation with clinical parameters in each of the three years. Only those children with consecutive samples for all three years were included in this analysis. Results We detected TSLP in 33% of 236 children for whom plasma samples were available for all three years. Overall, a consistently significant association was not found between TSLP and eczema or allergic sensitization. With regard to recurrent wheezing, children with detectable TSLP at one year of age were significantly less likely to experience recurrent wheezing by 3 years compared with those children without detectable TSLP, but this was only seen in children without aeroallergen sensitization at 3 years (P < 0.01). Conclusions and Clinical Relevance Contrary to our expectations, circulating TSLP was not significantly associated with eczema, allergen sensitization, or recurrent wheezing during the first three years of life. Early presence of circulating TSLP was significantly associated with reduced incidence of recurrent wheeze in those children not sensitized to aeroallergen. These findings suggest a possible underlying distinction between pathogenesis of developing atopic vs. non‐atopic recurrent wheeze.